Metabolic profiles of 2-oxindole-3-acetyl-amino acid conjugates differ in various plant species - Hladík, Pavel; Petřík, Ivan; Žukauskaitė, Asta; Novák, Ondřej; Pěnčík, Aleš (Frontiers in Plant Science, 2023)
Auxins are a group of phytohormones that play a key role in plant growth and development, mainly presented by the major member of the family -indole-3-acetic acid (IAA). The levels of free IAA are regulated, in addition to de novo biosynthesis, by irreversible oxidative catabolism and reversible conjugation with sugars and amino acids. These conjugates, which serve as inactive storage forms of auxin and/or degradation intermediates, can also be oxidized to form 2-oxindole-3-acetyl-1-O-ß-D-glucose (oxIAA-glc) and oxIAA-amino acids (oxIAA-AAs). Until now, only oxIAA conjugates with aspartate and glutamate have been identified in plants. However, detailed information on the endogenous levels of these and other putative oxIAA-amino acid conjugates in various plant species and their spatial distribution is still not well understood but is finally getting more attention. Herein, we identified and characterized two novel naturally occurring auxin metabolites in plants, namely oxIAA-leucine (oxIAA-Leu) and oxIAA-phenylalanine (oxIAA-Phe). Subsequently, a new liquid chromatography-tandem mass spectrometry method was developed for the determination of a wide range of IAA metabolites. Using this methodology, the quantitative determination of IAA metabolites including newly characterized oxIAA conjugates in roots, shoots and cotyledons of four selected plant models -Arabidopsis thaliana, pea (Pisum sativum L.), wheat (Triticum aestivum L.) and maize (Zea mays L.) was performed to compare auxin metabolite profiles. The distribution of various groups of auxin metabolites differed notably among the studied species as well as their sections. For example, oxIAA-AA conjugates were the major metabolites found in pea, while oxIAA-glc dominated in Arabidopsis. We further compared IAA metabolite levels in plants harvested at different growth stages to monitor the dynamics of IAA metabolite profiles during early seedling development. In general, our results show a great diversity of auxin inactivation pathways among angiosperm plants. We believe that our findings will greatly contribute to a better understanding of IAA homeostasis.